International ICT Research Collaboration: Experiences and Recommendations - PREM, Erich (Institutional Knowledge at Singapore Management University, 2011)
This paper presents results of a study into the collaboration experiences of researchers. The focus is on long-distance collaboration in information and communication technologies (ICT) research and technology development, i.e. between the EU on the one side and Australia, Singapore or New Zealand on the other. The aim of the study was to provide useful recommendations for researchers who engage in international collaboration and to improve the quality of international co-operation projects. The emphasis here is on the views and experiences of Europe"s international partners. The paper analysis collaboration motives, challenges, co-operation types and provides recommendations for project initiation, networking, consortium formation and proposal preparation as well as project execution. An important group of recommendations concerns project communication, travel and exchange visits and the cration of joint labs.